Pengaruh Metode Role Playing Pada Pembelajaran Qur'an Hadits Terhadap Sikap Tanggung Jawab Siswa Kelas IB Di MI Madinatunnajah Kota Cirebon - Syafitri, Anisa (UIN Siber Syekh Nurjati Cirebon, 2022)
Lack of innovation or learning methods during learning. So that it is less meaningful for the personal development and character of students, which results in the weak grasping power of students in understanding learning. The purpose of this study was to determine the effect of the role playing method on learning the Qur'an Hadith on students' responsible attitudes by using descriptive quantitative research methods. This research was conducted on fourth grade students at MI Madinatunnajah, Cirebon City. The research using the role playing method uses the observation method and the student's attitude of responsibility uses the questionnaire method. Data were analyzed using Simple Linear Regression Test assisted by SPSS 21 for windows. The research subjects were 20 students, while the data were collected using observation, questionnaires, and documentation. The results showed: (1) the process of implementing the role playing method went well, this was evidenced by the percentage of 75% with a mean of 50.5 and classified as high. (2) the attitude of students' responsibility belongs to the medium category, that is, 70% of the students are in the medium category. (3) there is an influence between the role playing method and the attitude of student responsibility where the value of tcount > ttable and the significant value is less than 0.05 so that Ha is accepted. So this shows that the role playing method for grade 4 students at MI Madinatunnajah has a positive influence on the attitude of responsibility.